Numerical Simulation of Landslide Triggered by Far-field Rain and Its Mitigation by Groundwater Control - AL-SUBAL, SHAMSAN SALEH HUSSEIN (2018)
Landslide is a major issue in tropical countries; the intensive rainfall is a main triggering factor for landslide that causes loss in lives and properties. In this study, the effect of rising of groundwater table in triggering landslide with respect to soil type, soil permeability and rain intensity in a regional scale were studied by running coupled seepage-slope analysis using SOILWORKS software.